Capital requirements, risk shifting and the mortgage market - Arzu Uluc; Tomasz Wieladek (European Central Bank (ECB), 2017)
We study the effect of changes to bank-specific capital requirements on mortgage loan supply with a new loan-level dataset containing all mortgages issued in the UK between 2005Q2 and 2007Q2. We find that a rise of a 100 basis points in capital requirements leads to a 5.4% decline in individual loan size by bank. Loans issued by competing banks rise by roughly the same amount, which is indicative of credit substitution. Borrowers with an impaired credit history (verified income) are not (most) affected. This is consistent with origination of riskier loans to grow capital by raising retained earnings. No evidence for credit substitution of non-bank finance companies is found.
Keywords: G21; G28; 330; Capital requirements; loan-level data; mortgage market; credit substitution